Factorise : r3/8 - s3/343 - t3/216 - 1/28 rst. -Maths 9th

1 Answer

Answer :

Solution  :-

Related questions

Description : Find the value of 1/27r3 - s3 + 125 t3 +5 rst, when s= r/3 + 5t. -Maths 9th

Last Answer : Solution :-

Description : Factorise 8x^3+343 -Maths 9th

Last Answer : 8x^3 + 343(2x)^3 + 7^3 Using identity a^3+b^3 = (a+b)(a^2 - ab +b^2 a=2x , b=7 (2x + 7)(4x^2 - 14x + 49). Further it is not factories. Thanks for reading. Please comment.

Description : 1:1, 8:4, 9:27, 64:16, 25:125, ?:?, 49:343, a) 36:316 b) 216:36 c) 316:16 d) 32:316 e) None of these

Last Answer : Its alternatively ratio of n2 and n3 Now, after 25:125, it would be 63 : 62  216:36 Answer: b)

Description : Evaluate each of the following: (i) 1113 – 893 (ii) 463 + 343 (iii) 1043 + 963 (iv) 933 – 1073 -Maths 9th

Last Answer : answer:

Description : Find the value of x, if(6/5)to the power x ,(5/6) to the power 2x = 125/216. -Maths 9th

Last Answer : Solution :-

Description : Find the value of: 4/(216)to the power -2/3 + 1/(256) to the power -3/4 + 2/(243) to the power -1/5. -Maths 9th

Last Answer : Solution :-

Description : Find the value of : 4/(216) to the power -2/5 + 1/(256) to the power -3/4 + 2/(243) to the power -1/5. -Maths 9th

Last Answer : Solution :-

Description : Find the value of x3-8y3-36xy-216 when x = 2y+6. -Maths 9th

Last Answer : Solution :-

Description : x^4+x^2+25 factorise this -Maths 9th

Last Answer : This answer was deleted by our moderators...

Description : Factorise each of the following expressions: -Maths 9th

Last Answer : (i) 48x3 - 36x2 = 12.4 x2 x - 12.3x2 = 12x2 (4x - 3) (ii) 5x2 - 15xy = 5x (x-3y) (iii) 15x3y2z - 25xy2z3 = 5xy2z(3x2 - 5z2)

Description : Factorise this question -Maths 9th

Last Answer : (i) The greatest monomial that is a common factor of the three terms is 6xy. ∴ 30x3y + 24x2y2 - 6xy = 6xy (5x2 + 4xy - 1) (ii) Here the polynomial (a-b) is a common factor. ∴ 5x(a-b) + 6y(a-b) = (a-b) (5x + 6y)

Description : Factorise this question -Maths 9th

Last Answer : (i) 7a3 + 7a - 2a2 - 2 = 7a(a2 + 1) - 2 (a2 + 1) = (a2 + 1) (7a - 2) (ii) The term of 4ax + 3by - 3ay - 4bx can be rearranged and factorized . 4ax - 4bx - 3ay + 3by = 4x(a-b) - 3y(a-b) = (a-b) (4x - 3y) (iii) x3 + y3 + x2y + xy2 = x3 + x2y + xy2 + y3 = x2(x+y) + y2 (x+y) = (x+y) (x2+y2)

Description : Factorise this question -Maths 9th

Last Answer : (i) 9x2 + 30xy + 25y2 = (3x2 + 2(3x) (5y) + (5y)2 = (3x + 5y)2 (ii) 9x2 - 30xy + 25y2 = (3x)2 - 2(3x) (5y) + 5y2 = (3x - 5y)2

Description : Factorise : x2 + 9x +18 -Maths 9th

Last Answer : Factorisation

Description : Factorise : 2x3 -3x2 -17x + 30 -Maths 9th

Last Answer : Factorisation of following

Description : Factorise the following : 9x2 -12x+ 3 -Maths 9th

Last Answer : Factorise the following :

Description : Factorise the following : 9x2 +4y2 + 16z2 +12xy-16yz -24xz -Maths 9th

Last Answer : Factorise the following

Description : Factorise the following -Maths 9th

Last Answer : Factorise the following

Description : Factorise : 1 + 64x3 -Maths 9th

Last Answer : Factorisation

Description : Factorise: a3 -8b3 -64c3 -24abc -Maths 9th

Last Answer : Factorisation

Description : Without finding the cubes, factorise (x- 2y)3 + (2y – 3z)3 + (3z – x)3. -Maths 9th

Last Answer : We know that, a3 + b3 + c3 – 3 abc = (a + b + c)(a2 + b2 + c2 -ab-bc-ca) Also, if a + b + c = 0, then a3 + b3 + c3 = 3abc Here, we see that (x-2y) +(2y-3z)+ (3z-x) = 0 Therefore, (x-2y)3 + (2y-3z)3 + (3z-x)3 = 3(x-2y)(2y-3z)(3z-x).

Description : x^4+x^2+25 factorise this -Maths 9th

Last Answer : This answer was deleted by our moderators...

Description : Factorise each of the following expressions: -Maths 9th

Last Answer : (i) 48x3 - 36x2 = 12.4 x2 x - 12.3x2 = 12x2 (4x - 3) (ii) 5x2 - 15xy = 5x (x-3y) (iii) 15x3y2z - 25xy2z3 = 5xy2z(3x2 - 5z2)

Description : Factorise this question -Maths 9th

Last Answer : (i) The greatest monomial that is a common factor of the three terms is 6xy. ∴ 30x3y + 24x2y2 - 6xy = 6xy (5x2 + 4xy - 1) (ii) Here the polynomial (a-b) is a common factor. ∴ 5x(a-b) + 6y(a-b) = (a-b) (5x + 6y)

Description : Factorise this question -Maths 9th

Last Answer : (i) 7a3 + 7a - 2a2 - 2 = 7a(a2 + 1) - 2 (a2 + 1) = (a2 + 1) (7a - 2) (ii) The term of 4ax + 3by - 3ay - 4bx can be rearranged and factorized . 4ax - 4bx - 3ay + 3by = 4x(a-b) - 3y(a-b) = (a-b) (4x - 3y) (iii) x3 + y3 + x2y + xy2 = x3 + x2y + xy2 + y3 = x2(x+y) + y2 (x+y) = (x+y) (x2+y2)

Description : Factorise this question -Maths 9th

Last Answer : (i) 9x2 + 30xy + 25y2 = (3x2 + 2(3x) (5y) + (5y)2 = (3x + 5y)2 (ii) 9x2 - 30xy + 25y2 = (3x)2 - 2(3x) (5y) + 5y2 = (3x - 5y)2

Description : Factorise : x2 + 9x +18 -Maths 9th

Last Answer : Factorisation

Description : Factorise : 2x3 -3x2 -17x + 30 -Maths 9th

Last Answer : Factorisation of following

Description : Factorise the following : 9x2 -12x+ 3 -Maths 9th

Last Answer : Factorise the following :

Description : Factorise the following : 9x2 +4y2 + 16z2 +12xy-16yz -24xz -Maths 9th

Last Answer : Factorise the following

Description : Factorise the following -Maths 9th

Last Answer : Factorise the following

Description : Factorise : 1 + 64x3 -Maths 9th

Last Answer : Factorisation

Description : Factorise: a3 -8b3 -64c3 -24abc -Maths 9th

Last Answer : Factorisation

Description : Without finding the cubes, factorise (x- 2y)3 + (2y – 3z)3 + (3z – x)3. -Maths 9th

Last Answer : We know that, a3 + b3 + c3 – 3 abc = (a + b + c)(a2 + b2 + c2 -ab-bc-ca) Also, if a + b + c = 0, then a3 + b3 + c3 = 3abc Here, we see that (x-2y) +(2y-3z)+ (3z-x) = 0 Therefore, (x-2y)3 + (2y-3z)3 + (3z-x)3 = 3(x-2y)(2y-3z)(3z-x).

Description : factorise (x-2y)^3-(x+2y)^3 -Maths 9th

Last Answer : NEED ANSWER

Description : factorise the following 4x^2+20x+25 -Maths 9th

Last Answer : NEED ANSWER

Description : factorise (x-2y)^3-(x+2y)^3 -Maths 9th

Last Answer : Given ( x - 2y) 3 + (2y - 3z) 3 + ( 3z - x) 3 Let a = ( x - 2y), b =(2y - 3z), c= ( 3z - x) a + b + c = ( x - 2y)+(2y - 3z)+( 3z - x) = 0 Recall that if (a + b + c) = 0 then a 3 + b 3 + c 3 = 3abc Thus, ( x - 2y) 3 + (2y - 3z) 3 + ( 3z - x) 3 = 3( x - 2y)(2y - 3z)( 3z - x)

Description : factorise the following 4x^2+20x+25 -Maths 9th

Last Answer : 4x^2+20x+25 4x^2+10x+10x+25 2x(2x+5)+5(2x+5) (2x+5)(2x+5) 2x^2+2(2x)(5)+25 2x^2+20x+25

Description : Factorise: 25/4.x(square) - y(square)/9. -Maths 9th

Last Answer : Solution :-

Description : Factorise: a(square) + b(square) - 2ba + 2bc - 2ca -Maths 9th

Last Answer : Solution :-

Description : Factorise: 2x(5) + 432x(square) y(cube). -Maths 9th

Last Answer : Solution :-

Description : Factorise: 125x3 + 27y3 + 8z3 - 90xyz. -Maths 9th

Last Answer : Solution :-

Description : Factorise: 2x(square) - 7x -15 by spliting the middle term. -Maths 9th

Last Answer : Solution :-

Description : Factorise :125x3 - 343y3. -Maths 9th

Last Answer : Solution :-

Description : Without finding the cubes, factorise: (2r-3s)3 +(3s -5t)3+ (5t-2r)3. -Maths 9th

Last Answer : Solution :-

Description : Factorise (9x -1/5)2 - (x + 1/3)2. -Maths 9th

Last Answer : Solution :-

Description : Using factor theorem, factorise the polynomial x3 + x2 - 4x - 4. -Maths 9th

Last Answer : Solution :-

Description : Factorise: x8 – y8. -Maths 9th

Last Answer : Solution :-

Description : Factorise: x3 +13x2 + 32x + 20. -Maths 9th

Last Answer : Solution :-

Description : Factorise: 2x3 - 3x2 - 17x + 30. -Maths 9th

Last Answer : Solution :-